Analisis Pemasaran Travel Umroh melalui Partnership dalam Meningkatkan Jumlah Jamaah di PT Amanah Safari Internasional Asafi Tour Bengkulu - Desi Fitriani; Yosy arisandi; Yosy arisand (Universitas Muhammadiyah Surabaya, 2025)
This study analyzes how Asafi Tour Kota Bengkulu's marketing strategy through partnership networks and its influence on the target market. This study focuses on the marketing and partnership aspects in Asafi Tour Kota Bengkulu travel. The purpose of the study was to determine the provisions of partnership (partners) in collaboration with Asafi Tour Kota Bengkulu travel in increasing the number of pilgrims and the marketing strategies carried out by Partners to increase the number of pilgrims. This study uses a qualitative approach with data collection through interviews, observations, and documentation. The results of the study indicate that the agreed partnership provisions are stated in the Company's SOP and include the use of ID cards, timestamp photos, closing targets, promotions on social media, and work progress reports. The marketing strategies used by Asafi Tour Partners include a proactive approach such as building good relationships with religious and community leaders, providing quality Umrah packages, utilizing social media, and participating in religious study activities. This study concludes that clear and structured partnership provisions, as well as appropriate and integrated marketing strategies, help Asafi Tour Bengkulu increase credibility and expand its market reach. Comprehensive marketing analysis, including market analysis, competitors, potential partners, and financial analysis, is the key to the success of an Umrah travel partnership.